2021
DOI: 10.21203/rs.3.rs-1166456/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How Much Obesity and Diabetes Do Impair Male Fertility?

Abstract: BackgroundSubfertility in obese and diabetic men during the reproductive age is evident, but the mechanisms by which obesity and diabetes mellitus cause male infertility are not entirely understood. The current study aimed to evaluate the effects and potential mechanisms of obesity and diabetes on male fertilityMethodsWe enrolled control=40, obese=40, Lean-DM=35, and Obese-DM=35 individuals. The obesity-associated markers, diabetic markers, hormonal and lipid profile, inflammatory indices, and semen analysis w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…They also found no significant correlation between BMI and sperm concentration, normal morphology, and progressive motility [ 40 ]. According to Abbasihormozi et al, high BMI was negatively correlated with sperm normal morphology, sperm motility, progressive motility, and sperm count [ 41 ]. Contrary to our results, Pooladi et al reported a negative correlation between BMI and sperm motility (overall or progressive) but not sperm morphology and count [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also found no significant correlation between BMI and sperm concentration, normal morphology, and progressive motility [ 40 ]. According to Abbasihormozi et al, high BMI was negatively correlated with sperm normal morphology, sperm motility, progressive motility, and sperm count [ 41 ]. Contrary to our results, Pooladi et al reported a negative correlation between BMI and sperm motility (overall or progressive) but not sperm morphology and count [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies with interesting results have been conducted since the aforementioned meta-analyses [39][40][41][42]. For example, in a cross-sectional study, Esmaeili et al found that BMI was negatively correlated with normal sperm morphology, sperm total motility, and progressive motility, but it had no effect on sperm volume and concentration.…”
Section: Discussionmentioning
confidence: 99%